Plant Extracts as Potential Acaricides for the Management of Red Spider Mite, Oligonychus coffeae Nietner (Acarina: Tetranychidae), in the Tea Ecosystem: An Eco-Friendly Strategy - Deka, Bhabesh; Babu, Azariah; Baruah, Chittaranjan; Sarkar, Suman (Frontiers in Agronomy, 2022)
The effect of application of aqueous extracts of selected five traditional plants like (Murraya paniculata, Cassia tora, Amphineuron opulentum, Tithonia diversifolia and Cassia alata) were compared with that of synthetic acaricide in reducing the population of red spider mite, Oligonychus coffeae, a major pest of tea, besides their impact on natural enemies and green leaf yield. Analysis of large scale field trials showed that, all the five plants extract treatments resulted in similar yield was analogous to the application of synthetic acaricide. Reduction of pest population was observed at par to the synthetic acaricide with higher number of natural enemies in pesticidal plant extract treated plots in comparison to the synthetic acaricide treated plot which indicated less impact of pesticidal plants on natural enemies. Phytotoxicity study on tea leaves indicated that aqueous extracts of selected plants are non-phytotoxic and do not impart any taint to the made tea samples. Therefore, the present investigation encourage that, plant extracts used as a botanical pesticide shows the toxicity against tea red spider mite without harming the beneficial insects, increase the yield devoid of any lethal consequence on tea plants or consumers.